2003
DOI: 10.1557/jmr.2003.0028
|View full text |Cite
|
Sign up to set email alerts
|

Phase stability of B2O3-added Ba2Ti9O20 ceramic: Processing effects

Abstract: Preparation of dense and phase-pure Ba2Ti9O20 is generally difficult to achieve using solid-state reaction, since there are several thermodynamically stable compounds in the vicinity of the desired composition. This study investigated the effects of B2O3 on the densification, microstructural evolution, and phase stability of Ba2Ti9O20. Samples from the host material (2BaO · 9TiO2) with and without the addition of 5 wt% B2O3 were prepared through different processing routes. For the pure host material sintered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In the case of the specimen sintered at 800 • C with BaB 2 O 4 addition, no considerable change in phase evolution was observed when compared with the calcined powders. However, as the sintering temperature increased, the dominant BaTi 4 O 9 phase produced at the low sintering temperature of 800 • C disappeared and the Ba 2 Ti 9 O 20 phase was mainly obtained with a minor amount of BaTi(BO 3 shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the specimen sintered at 800 • C with BaB 2 O 4 addition, no considerable change in phase evolution was observed when compared with the calcined powders. However, as the sintering temperature increased, the dominant BaTi 4 O 9 phase produced at the low sintering temperature of 800 • C disappeared and the Ba 2 Ti 9 O 20 phase was mainly obtained with a minor amount of BaTi(BO 3 shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that the addition of B 2 O 3 has the advantages of lowering sintering temperatures and improving dielectric properties of Ba 2 Ti 9 O 20 . 3,4 It was also reported that B 2 O 3 addition could enhance the formation of Ba 2 Ti 9 O 20 . However, chemical reaction between the glass and ceramics should be considered because reaction induced compositional change or development of second phases might deteriorate the dielectric properties.…”
Section: Introductionmentioning
confidence: 97%
“…Recent research trend suggests that glass addition is a useful method of producing low loss ceramics like (Zr,Sn)TiO 4 , Ba 2 Ti 9 O 20 , Ba(Mg 1/3 Ta 2/3 )O 3 , Ca 5 Nb 2 TiO 12 , BaTi 4 O 9 , 0.83ZnAl 2 O 4 -0.17TiO 2 , Mg 2 SiO 4 , etc. at low sintering temperatures [10][11][12][13][14][15][16][17][18][19][20][21]. However, majority of ceramic-glass systems offer relatively inferior dielectric properties compared to those of high temperature firing systems.…”
Section: Introductionmentioning
confidence: 99%
“…The complex procedures involved, the high cost of the chemicals, and poor microwave dielectric properties preclude the use of chemical synthesis for the industrial production of DRs 25 . Recent researches suggest that the addition of glassy materials as sintering aids is the most effective and simple method available to attain the above‐mentioned goals, as has been experimentally shown with low loss DR materials like (Zr, Sn)TiO 4 26,6 Ba 2 Ti 9 O 20 , 27–29 BaTiO 4 , 30–32 (Mg 0.5 Ca 0.5 )TiO 3 , 33–35 BiNbO 4 , 36 and Ba(Mg 1/3 Ta 2/3 )O 3 37–39 . However, for most of the systems with a higher amount of glass or a mixture of additives, the reduction of sintering temperature is usually accompanied by an abrupt decrease of physical and dielectric properties of the matrix material because of the formation of secondary phases 40 .…”
Section: Introductionmentioning
confidence: 99%